Optimal inequality behind the veil of ignorance - Che-Yuan Liang (Uppsala University, Department of Economics, 2013)
In Rawls' (1971) influential social contract approach to distributive justice, the fair income distribution is the one that an individual would choose behind a veil of ignorance. Harsanyi (1953, 1955, 1975) treats this situation as a decision under risk and arrives at utilitarianism using expected utility theory. This paper investigates the implications of applying prospect theory instead, which better describes behavior under risk. I find that the specific type of inequality in bottom-heavy right-skewed income distributions, which includes the log-normal income distribution, could be socially desirable. The optimal inequality result contrasts the implications of other social welfare criteria.
urn:nbn:se:uu:diva-199754
Keywords: D63; D03; D31; D81; 330; veil of ignorance; prospect theory; social welfare function; income inequality